Pengaruh Perubahan Dalam Meningkatkan Produktivitas Jual Beli Untuk Memenuhi Kepuasan Pelanggan pada Toko Helm Cabang Taplau - Fauziah, Amirah; Putri, Bunga Henida; Islamy, Zahra Nadhira; Putra, Ramdhani Bayu; ., Fitriyani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This Community Service aims to determine the effect of changes in increasing buying and selling to meet customer satisfaction at the Taplau Helmet Shop. Changes are very influential in the productivity of buying and selling in this shop, especially changes in weather conditions, good productivity really determines customer satisfaction. Problems found when conducting research are: sales and purchases at this shop are uncertain, there are many competitors who have similar businesses. The solution to this problem is to increase sales both offline and online, set a wiser strategy, provide more varied prices than competitors. This article was prepared by observation, collecting data in interviews, and documentation. The research results show that customer satisfaction depends on the buying and selling productivity provided by the shop